2020
DOI: 10.1002/psp.2418
|View full text |Cite
|
Sign up to set email alerts
|

Geography, psychology and the ‘Big Five’ personality traits: Who moves, and over what distances, in the United Kingdom?

Abstract: Personality, as measured by the ‘Big Five’ dimensions of agreeableness, openness, extroversion, neuroticism and conscientiousness, has been explored in the social psychological literature as a predictor of migration but so far has received very little attention in the geographical literature, which is surprising given its predictive importance and also evidence that the selectivity of migration shapes area personality profiles. Using the Understanding Society1 data set, this paper analyses how personality infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…A grow ing body of work from the psy cho log i cal lit er a ture sug gests that inter nal and inter national migrants exhibit dif fer ent per son al ity traits than the gen eral pop u la tion. Recent stud ies from Australia, the United States, and Europe found that indi vid u als who score high on open ness are more likely to migrate (Campbell 2019;Fouarge et al 2019;Jokela 2009Jokela , 2014Shuttleworth et al 2020), although there is no agree ment on the effect of other per son al ity traits on migra tion behav ior. The HILDA Survey captures the Big Five per son al ity traits only every four years.…”
Section: Modeling Strategymentioning
confidence: 99%
“…A grow ing body of work from the psy cho log i cal lit er a ture sug gests that inter nal and inter national migrants exhibit dif fer ent per son al ity traits than the gen eral pop u la tion. Recent stud ies from Australia, the United States, and Europe found that indi vid u als who score high on open ness are more likely to migrate (Campbell 2019;Fouarge et al 2019;Jokela 2009Jokela , 2014Shuttleworth et al 2020), although there is no agree ment on the effect of other per son al ity traits on migra tion behav ior. The HILDA Survey captures the Big Five per son al ity traits only every four years.…”
Section: Modeling Strategymentioning
confidence: 99%
“…Paulauskaitė et al (2010) and Tabor et al, (2015) found that the relation between conscientiousness and the intention to move to another country was negative. On the contrary, Shuttleworth et al (2021) found that individuals with high consciousness scores are more likely to expect to move next year. However, Jokela (2009) found no association between conscientiousness and migration.…”
Section: The Role Of Personality In Real-world Migration Intentionsmentioning
confidence: 87%
“…Therefore, extraversion is a trait relevant to migration (Canache et al, 2013). In many studies, higher levels of extraversion have been found to be connected with a higher propensity for migration intention and migration (Paulauskaite et al, 2010, Campbell, 2019, Shuttleworth et al 2021, as well as successful living adjustment and interaction adjustment (i.e. interactions with people in the migration country) (Huang et al, 2005).…”
Section: The Role Of Personality In Real-world Migration Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having said that, we suspect that there is a good deal of selection and self-selection in geographic mobility that, in turn, might be associated with people's outlook and worldview. For example, Shuttleworth et al (2020) report that individuals scoring high on the personality trait of openness to new experience are more likely to make a long-distance move of at least 50 km. Chan (2019) report that openness is correlated with cultural omnivorousness, which is a strong predictor for Remain-support (Chan et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%